The simple method of dynamic visco-elastic analysis of road structure. on rheological foundation - Sławomir Karaś; Magdalena Sawecka (Budownictwo i Architektura, 2009)
In contrast to computationally advanced methods of road pavement dynamic analysis, the one-dimensional, simple method is derived on the basis of visco-elastic simple beam lying on generalized Winkler visco-elastic foundation. By virtue of least square method the visco-elastic constants could be estimated with technically admissible accuracy. The introduced method is useful enough to predict any pavement deformation process in the range of linear visco-elasticity.